Quality of Live Improvement Antituberculosis Consumer - Jumasni Adnan (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2019)
Antituberculosis is the most liver damage causes. Rifampicin and Isoniazide, in combination, are toxic compounds. Isoniazide and rifampicin metabolits causes lipid peroxidation. The hepatoprotective effect of rosella calyx water extract on liver damage induced with Isoniazide-rifampicin evaluated by examination of malondialdehid levels in the liver organ. 25 male wistar rats divided into 5 groups, ie group I (INH-rifampicin + rosella water extract 250 mg/kgBW), group II (INH-rifampicin + rosella water extract 125 mg/kgBW), group III (INH-rifampicin + rosella water extract 62.5 mg/kgBW),  group IV (healthy control) and group V (Isoniazide-rifampicin). MDA liver levels were analyzed after 35 days of treatments. The test results of each group are, group I has mean MDA levels 0.023912 + 0.011 mg/ml, group II 0.023526 + 0.009 mg/ml, group III 0.027168 + 0.007 mg/ml group IV 0.03437 + 0.009 mg/ml and group V 0.236846 + 0.118 mg/ml. The kruskal-wallis test showed significantly value 0.008 (p <0.05) and Post hoc Mann U whitney test showed that group V was significantly different to group I, II, III, and IV (p = 0.008) respectively, roselle extract can be used as a hepatoprotector antioxidant to improve the tuberculosis drug consumer quality of life through improved health by lowering lipid peroxidation that causes liver damage.